Kajian Konsentrasi Logam Merkuri (Hg) Pada Tanah Dan Serapan Tanaman Pangan Di Sekitar Kelurahan Poboya - Caco, Caco; Darman, Saiful; Isrun, Isrun (Mitra Sains, 2021)
Food crops are agricultural products consumed to support our daily lives. Food plants are also a source of vitamins and minerals needed by our bodies and directly play a role in improving health. Therefore, the hygiene and safety of the food we consume is very important, not to cause health problems. Soil is an importantfactor in agriculture, as a medium to grow plants and is also a part of the cycle of heavy metals. The gold mining business is often seen as the cause of environmental damage and pollution. This research was conducted at food and secondary crops farms around Poboya, where soil and plant analysis was carried out at the Laboratory of Natural Resources and Environment, Faculty of Agriculture, Tadulako University, Palu. The research was conducted from September to November 2020. The method used was survey with field observations and laboratory analysis, gradually done through pre-survey, main survey (sampling) and laboratory analysis with tactical sampling. The results showed that mercury (Hg) concentration in the sample point 1 was 0.48 - 0.52 ppm, sample point 2 was 0.62 - 0.63 ppm, sample point 3 was 0.30 - 0.35 ppm and sample point 4 is 0.25 - 0.26 ppm. While the concentration of mercury (Hg) in food crops, namely: sample point 1 is 0.31 - 0.33 ppm, sample point 2 is 0.45 - 0.48 ppm, sample point 3 is between 0.20 - 0.24 ppm and sample point 4 around 0.09 - 0.10 ppm. This shows that the content of heavy metal mercury (Hg) in the soil around Poboya has passed the tolerable threshold. Meanwhile, the concentration of mercury (Hg) in food crops at points 1 and 2 passed the critical threshold, while sample points 3 and 4 were still below the critical threshold. The farther the distance from the processing site, the less mercury content in the soil and in food crops.